Successful Treatment in a Case of Massive Hepatocellular Carcinoma with Paraneoplastic Syndrome - Atsunori Tsuchiya (Case Reports in Gastroenterology, 2009)
Paraneoplastic syndromes of hepatocellular carcinoma (HCC) are not uncommon. However, the prognosis is poor and follow-up and improvement of paraneoplastic syndromes with treatment have been reported rarely. We report a successful case in an aged man of a massive HCC with paraneoplastic syndrome, treated by combined intraarterial chemotherapy and hepatic resection. Paraneoplastic syndrome (erythrocytosis and hyperlipidemia) was monitored throughout the treatment and erythropoietin (EPO) mRNA also was analyzed in the resected liver. The hemoglobin level and serum levels of EPO and total cholesterol (T-cho) decreased dramatically with treatment, along with a decrease in serum levels of α-fetoprotein and protein induced by vitamin vitamin K absence II (PIVKA-II). Semiquantitative reverse transcription polymerase chain reaction (RT-PCR) revealed that the residual cancer expressed EPO RNA but the nontumor tissue did not. This was a rare case of paraneoplastic syndrome of HCC that was treated successfully. This case indicates that paraneoplastic syndrome reflected tumor progression and that serum levels of both EPO and T-cho might be used as tumor markers.